Study The Relation Between Toxoplasma gondii and Biochemical Parameters in Pregnant Women - Breesam, Basim Kadhim; Lafta, Rehab Faisal (Scientific Journal of Medical Research, 2020)
Objectives: Toxoplasma gondii is one of the internal parasites which live in some kinds of tissues, such as muscles and intestinal epithelium, and infection may be congenital. the congenital form is more severe when maternal infection occurs early in pregnancy. Methods: Samples of pregnant women suffers from Toxoplasma gondii from alkafeel hospital that was about 22 specimens is collected to check if pregnant women with Toxoplasma gondii infection has alteration in some of their biochemical parameters ( creatinine, ALT , AST, cholesterol ). Results: The current study aims to show the effectiveness acute of toxoplasmosis on some liver and kidney parameters. The result came close to normal, and there was no significant change in those biochemical criteria. Some were high and others were low. Conclusion: Toxoplasma gondi does not have strong relation with the biochemical parameters in pregnant women in different group of ages.